Objects as habitats of various pathogens in the hunting-ground - Tucak, Zvonimir; Periškić, Marin; Krznarić, Marko; Florijančić, Tihomir; Grubešić, Marijan; Bošković, Ivica (Acta Agraria Kaposváriensis, 2002)
Continuous monitoring in 2001 and 2002, of the microflora abundance at several objects, vehicles, trees and water bodies in the hunting-ground Mackovac, indicated the presence of several micro-organisms during the whole time period. Thus the infections in wild-game populations is made possible by this pathogens. Disinfecting measures concerning the exclusion of the infection are required in the maintenance of the zoohygienic conditions in the hunting-ground.